2015
DOI: 10.1007/s40744-015-0008-9
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics Associated with Biologic Monotherapy Use in Biologic-Naive Patients with Rheumatoid Arthritis in a US Registry Population

Abstract: IntroductionThe aim of this study was to describe factors associated with initiating a biologic as monotherapy vs in combination with a conventional disease-modifying antirheumatic drug (DMARD) in biologic-naive patients with rheumatoid arthritis (RA) enrolled in the Corrona registry.MethodsFirst biologic initiations were classified as monotherapy (Bio MT) or combination therapy (Bio CMB). Baseline demographic and clinical characteristics were evaluated. Odds ratios (OR) based on mixed effects regression model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 19 publications
(20 reference statements)
3
15
1
Order By: Relevance
“…While our design did not account for all possible unmeasured confounders, when the set of measured demographics were compared for the two groups, no significant differences were present. In addition, our cohort was similar to the validation cohort (Hill et al, 1992) and other inflammatory arthritis cohorts (Bykerk et al, 2012;Pappas et al, 2015) that reported similar results. Taken together, these findings add credence to our interpretation that, despite the potential existence of uncontrolled confounders, there is a positive relationship between collaborative care models and patient satisfaction.…”
Section: Discussionsupporting
confidence: 84%
“…While our design did not account for all possible unmeasured confounders, when the set of measured demographics were compared for the two groups, no significant differences were present. In addition, our cohort was similar to the validation cohort (Hill et al, 1992) and other inflammatory arthritis cohorts (Bykerk et al, 2012;Pappas et al, 2015) that reported similar results. Taken together, these findings add credence to our interpretation that, despite the potential existence of uncontrolled confounders, there is a positive relationship between collaborative care models and patient satisfaction.…”
Section: Discussionsupporting
confidence: 84%
“…Rituximab is approved only with MTX in the USA and Europe 97 98. Two recent analyses of the CORRONA registry showed the likelihood of starting biologic monotherapy was consistently increased if it was approved for use as monotherapy 44 99. Other factors that increased the likelihood of a biologic monotherapy prescription included the patient's previous biologic experience and the rheumatologist's prescribing patterns.…”
Section: Biologic and Oral Dmard Monotherapymentioning
confidence: 99%
“…In our experience we could observe that the frequency of monotherapy was 31.6%, somewhat higher than that observed in a multicentric Argentine study where the frequency was 21.4% [24]. Global records inform that the use of monotherapy varies between 12 and 39% [25,26].…”
Section: Discussionmentioning
confidence: 42%